Evaluasi Kecukupan Panas Proses Pasteurisasi Saus Tomat di PT XYZ dan Dampaknya terhadap Umur Simpan - Mahdiyar, Dewangga; Purnomo, Eko Hari; Hermanianto, Joko (Jurnal Teknologi dan Industri Pangan, 2024)
Tomato sauce is typically thermally processed to achieve a sufficient level of microbial destruction, particularly vegetative microorganisms, which could pose risks to public health. This process is crucial when food is stored, distributed, resold, and consumed by end-users. The aim of this study was to evaluate the thermal processing adequacy of tomato sauce, determine the optimal cooking duration for achieving high product quality for PT XYZ, and assess its impact on the product's shelf life. The study was conducted in three stages: measuring the product temperature in the cooker tank, evaluating pasteurization adequacy based on pasteurization value (P85) calculations and organoleptic testing of the tomato sauce, and estimating its shelf life. The cooking process of tomato sauce at PT XYZ showed that the pre-heating stage required 62.4 min to reach 90 °C, holding time at 90 °C was 15.5 min, and cooling the product to 70 °C took 52 min. The pasteurization value (P85) of the tomato sauce at PT XYZ was deemed excessively high. Pasteurization at 90 °C for 1 sec produced tomato sauce with quality attributes (color, taste, aroma, and viscosity) preferred by panelists compared to tomato sauce pasteurized at 90 °C for 15.5 min. Additionally, this duration was sufficient to inactivate vegetative cells of molds and yeasts, Escherichia coli, Salmonella, and Listeria monocytogenes. Based on viscosity as a quality attribute, the shelf life of tomato sauce pasteurized at 90 °C for 1 sec and stored at 30 °C was 367 days, whereas tomato sauce pasteurized at 90 °C for 15.5 min had a shelf life of 137 days.